Crimes violentos letais intencionais: ocorrências em Curitiba (2012-2019) analisadas a partir das divisas dos seus bairros e indicadores sociais - Lobo, Gerson Luis de Almeida (2021)
The intentional lethal violent crimes (ILVC), i. e., those that result in the victim’s life loss due to an external, violent and willful cause are a severe social problem in Brazil for decades, with many social repercussions. In the latest global data available, the country leads the rank of registered victims in these conditions. This master’s dissertation aims to study this phenomenon from a municipal perspective, understanding this federative entity as a space as theorized by Milton Santos, that is, an inseparable set of object systems and action systems. After presenting a diagnosis of this issue at a national level, this criterion was selected to understand the way the ILVC are distributed across the cities – whether inside its limits or in the dynamics with neighboring municipalities – and how these federative entities can take actions to preserve the lives of its citizens. Public security at city scale is a very specific challenge, since the competences for policing and crime investigation belong to police forces linked to State Government. Therefore, City Halls do not directly decide where and how policing will take place. The case of Curitiba Metropolitan Area was chosen as object of study, with data from 2012 to 2019. During this period, Curitiba concentrated most of the violent deaths in its State, but also showed a notable reduction in the records, a trend also verified in its neighbor cities. The aim is, thus, to explore the distribution of the ILVC in Curitiba’s territory, to study how the local scenario is related with the state and national contexts and which facts and/or social indicators may have correlation with Curitiba’s portrait. This dissertation took data from the State Secretariat for Public Security of Paraná, the Brazilian Unified Health System, Brazilian Institute of Geography and Statistics and Curitiba’s Urban Planning Institute to carry out the proposal, which includes the presentation of thematic maps to compare the distribution of ILVC inside city’s territory with diverse variables. Correlations between concentration of ILVCs and worst social indicators (lower family income and education, higher housing density), younger population and larger black population were found in Curitiba’s neighborhoods.